Agrifood Supply Chain Traceability: A Systematic Literature Review - Ahmed, Shehzad; Razak, Ghadafi Muhmar; Rafi-Ul-Shan, Piyya Muhammad; Naeem, Saira; Mehmood, Amina; Kourouklis, Athanassios; Ayyub, Rana Muhammad (International Journal of Supply Chain Management, 2021)
This paper investigates the knowledge gaps in the published research on agri-food supply chain traceability (AFSC), identifies the main unexplored issues and potential research gaps, and sets the research agenda for future researchers. A systematic literature review of the quality work/papers on AFSC traceability was done for the period (2008-2020) using a PRISMA flow diagram. The systematic literature review results have provided insight into the present literature and set future research directions related to agri-food supply chain traceability-related to re-search. The study reveals several critical issues related to all the stakeholders; it has furthered understanding of drivers and challenges and Food Traceability System contributions from a practical perspective. This paper has used only quality research work of 12 years only as per set inclusion and exclusion criteria which is the study’s main limitation. It identifies significant knowledge gaps and defines directions for future research. This work has explored the current state of the regulations and potential technologies to help effective decision-making practices that managers can use in AFSCs.This study has presented an idiosyncratic set of research domains for further investigation in the area